Emergence of Mpox and new epidemics: psychological and social impact of stigma in communication and prevention - Giacomo Fiacco; Antonietta Grandinetti (Emergency Care Journal)
Emerging viral epidemics are increasingly being studied and monitored. In addition to the strictly virological and symptomatic aspects, there is a growing recognition of the need to address the psychological dimension of the patient. The humanization of care should now be an integral part of clinical practice. However, the risk of stigmatization associated with infections that cause epidemics is more real than ever. This is of particular concern as it can negatively impact the prevention and management of the infection due to perceived judgment from healthcare providers and society. An integrated and targeted approach that considers the psychological aspect and the mental fragility of patients can improve screening and prevent the potential risk of stigmatization.